Semantic Analysis of Daud Kamal’s ‘A Street Revisited’, ‘Transition’ and ‘The Rebel’ - Atta, Aqsa; Fatima, Syeda Asia; Afzal, Malik Haroon (Pakistan Languages and Humanities Review, 2023)
The study of meaning plays an important role in analyzing and examining the text. The study aims to interpret and analyze Daud Kamal’s three selected poems. By using Leech’s theoretical framework (1981) the study analyzes how the study of meanings at different levels helps readers to understand the contextual background of the selected poems. The findings reveal that the contextual background of the poems is well understood through conceptual, contextual, reflected, and thematic meaning. Moreover, collocative and stylistic meaning in the poems clearly show the cultural identity of Daud Kamal as a Pakistani poet. The frequency of different meanings in the poems reflects that all the poems have one conceptual meaning, but the predominant meanings include connotative and collocative meaning. Through these meanings, readers can understand poet’s approach to the ultimate truth of social and cultural change.